The Effect of Artificial Intelligence–Based Learning on Students’ Mathematical Thinking in Secondary Education - Monoko Haguchi; Nur Chalim Wachidah; Gandha Satria Adi; Fitri Irawijayanti; Fatqurhohman Fatqurhohman (JINEA: Journal of Innovation in Education and Learning, 2026)
The rapid integration of artificial intelligence (AI) in secondary education has transformed mathematics learning through adaptive and personalized instructional support. This study investigates the effect of AI-based learning on students’ mathematical thinking by comparing AI performance with student performance across different mathematical problem types. A quantitative experimental–comparative design with a pretest–posttest control group approach was employed, involving 120 secondary school students assigned to experimental and control groups. The experimental group engaged in AI-assisted learning using ChatGPT, while the control group received conventional instruction. Mathematical thinking was assessed using accuracy, response time, and consistency across multiple-choice, short-answer, and essay tasks, with digital literacy examined as a mediating variable. The results reveal significant performance differences, with AI demonstrating higher accuracy, faster response times, and greater consistency, particularly on essay-based problems requiring higher-order reasoning. Mediation analysis further indicates that digital literacy significantly influences students’ mathematical thinking and partially mediates the relationship between AI interaction and learning outcomes. These findings suggest that AI-based learning can effectively enhance mathematical thinking when integrated with strong digital literacy development, highlighting implications for adaptive pedagogy and future longitudinal research.